2016
DOI: 10.15389/agrobiology.2016.5.722eng
|View full text |Cite
|
Sign up to set email alerts
|

GENETIC STRUCTURE OF REGIONAL POPULATIONS OF Mycosphaerella graminicola (Septoria tritici), THE SEPTORIA LEAF BLOTCH AGENT OF WHEAT

Abstract: Mycosphaerella graminicola (anamorph Septoria tritici), the causal agent of septoria tritici blotch (STB) of wheat, is dominating species in Septoria/Stagonospora complex on crops in the main grain-producing areas of Russia. Resistance to STB may be either quantitative (horizomtal) or isolate-specific (vertical). At present 17 genes for resistance have been identified (Stb1-Stb17). The genfor-gen interaction in the «wheat-M. graminicola» pathosystem has been demonstrated by genetic analysis; therefore, the avi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
1
6
0
1
Order By: Relevance
“…In Russia, Septoria blotch holds a dominant position in a pathogenic complex of fungus diseases of wheat plantings. The disease poses the highest priority danger in Central, Southern, North Caucasian, North-Western, Privolzhsky, and Siberian Federal regions [16][17][18]. In epiphytotic years, the crop losses from the disease can reach 20-40 % [19][20][21][22][23].…”
mentioning
confidence: 99%
“…In Russia, Septoria blotch holds a dominant position in a pathogenic complex of fungus diseases of wheat plantings. The disease poses the highest priority danger in Central, Southern, North Caucasian, North-Western, Privolzhsky, and Siberian Federal regions [16][17][18]. In epiphytotic years, the crop losses from the disease can reach 20-40 % [19][20][21][22][23].…”
mentioning
confidence: 99%
“…[6] Research conducted by Pakholkova et al [7] showed that 6 of the 8 of known resistance genes (Stb1-Stb5, Stb7) had only partial functionality in natural populations of M. graminicola in Russia, the Stb6 gene was highly effective against five populations of M. graminicola. The Stb8 gene was efficient in absolute sense against all tested isolates.…”
Section: Original Articlementioning
confidence: 99%
“…Evaluation of Stb1-Stb8 gene effectiveness in the European part of Russia showed that only two of them (Stb6 and Stb8) provided resistance to all populations of Z. tritici, three (Stb2, Stb3 and Stb4) to individual regional sub-populations, and the remaining genes had already been overcome by the pathogen [26]. These data indicate that the set of Stb genes available for breeding is very limited.…”
Section: Introductionmentioning
confidence: 98%